Pembinaan Karakter Gemar Membaca di Sekolah Dasar Negeri - Lili Kurniasih; Syarnubi; Achmad Fadil; Gerry Krzic (PAI RAFAH, 2025)
This study explores strategies to develop reading habits among students at SDN 8 Tanjung Lago Banyuasin and the challenges faced. Reading plays a vital role in intellectual and character development, yet students' reading habits remain low. Using a qualitative approach through observations, interviews, and documentation, the study finds that while literacy programs like daily reading sessions and classroom reading corners exist, they have not fully established a strong reading culture. Challenges include a lack of engaging books, tight academic schedules, minimal parental support, and the distraction of digital entertainment. To address this, schools enhance teachers' roles as literacy facilitators, engage parents in literacy programs, and integrate digital resources. Strategies such as book discussions, storytelling, and reward systems create a more engaging environment. Findings highlight the need for collaboration between schools, teachers, and parents to nurture lifelong reading habits, supporting students' academic success and personal growth.